Spin Off Feasibility Study of Sharia Financing Unit: Study in Adira Finance - Lita Wulandari; Hermanto Siregar; Hendri Tanjung (Al-Iqtishad: Jurnal Ilmu Ekonomi Syariah, 2018)
The Financial Services Authorization (OJK) as the regulator of the finance industry has issued a policy set forth in the POJK. 28 / POJK.05 / 2014 which explains that multi-finance which has sharia portfolio as much as 50% from total business or five years from POJK is lawfully obliged to do spin-off sharia. With this policy, sharia business unit can be more focus on business development. Through this research will be analyze the feasibility of sharia financing business unit in fulfilling the aspect of separation of business unit (spin-off). Beside by observation, deep interview with Sharia Supervisory Board (DPS) and literature review, the research also use ARIMA and Double Smoothing Exponential to forecast market and financial aspect. Based on the research results sharia financing unit of Adira Finance has the ability to be spin off. But it should be noted from technology and human resources aspects.DOI: 10.15408/aiq.v10i2.5781